Deep learning-based semantic segmentation of remote sensing images: a review - Lv, Jinna; Shen, Qi; Lv, Mingzheng; Li, Yiran; Shi, Lei; Zhang, Peiying (Frontiers in Ecology and Evolution, 2023)
Semantic segmentation is a fundamental but challenging problem of pixel-level Remote Sensing (RS) data analysis. Semantic segmentation tasks based on aerial and satellite images play an important role in a wide range of applications. Recently, with the successful applications of Deep Learning (DL) in the Computer Vision (CV) field, more and more researchers have introduced and improved DL methods to the task of RS data semantic segmentation and achieved excellent results. Although there are a large number of DL methods, there is still a lack of method review and progress on semantic segmentation of RS data. To solve the problem, this paper surveys more than 100 papers in this field in the past five years and elaborates in detail on the aspects of technical framework classification discussion, datasets, experimental evaluation, research challenges, and future research directions. Different from several previously published surveys, this paper first focuses on comprehensively summarizing the advantages and disadvantages of techniques models according to the important and difficult points. This research will help beginners quickly establish research ideas and processes in this field, enabling them to focus on algorithm innovation without paying too much attention to datasets, evaluation indicators, and research frameworks.